Intra- and intermolecular interactions mediated by adaptor protein Ruk/CIN85/SETA - Ilnytska, O.M.; Drel, V.R.; Shuvayeva, H.Yu.; Havrylov, S.V.; Fedyshyn, Ya.Ya.; Mayevska, O.M.; Ihumentseva, N.I.; Gout, I.T.; Buchman, V.L. (Біополімери і клітина, 2005)
Ruk/CIN85l SETA is a member of a separate and evolutionary conserved family of adapter I scaffold proteins implicated in apoptic and receptor tyrosine kinases signalling, rearrangement of actin cytoskeleton and cell adhesion, podocyte and T cell functions. Self-regulation through intra- and intercellular interactions can be supposed for RuklCIN85l SETA as this protein contains SH3 domains and proline-rich sequence, localized within one polypeptide chain, as well as C-terminal coiled-coil region. The ability of Ruk proline-rich motifs to interact with its own SH3 domains in an intramolecular fashion and coiled-coil region to mediate oligomerization between different isoforms was assessed in GST pull down experiments. It was shown that both Ruk SH3A and to a less extent SH3B domains can interact with its own proline-rich sequences in a cooperative manner, while coiled-coil region provide for isoforms oligomerization. SH3C domain appear exerts conformational constraints, imposed on coiled-coil region, restricting the level of oligomerization. We also demonstrated that the ability of exogenous ligands to interact with Ruk polyprotine motifs is changing during the course of TNFa-induced apoptosis of human myelomonocytic W37 cells. RuklCIN85lSETA є представником окремої еволюційно консервативної родини адаптернихі риштувальних білків, залучених до апоптичного сигналювання і сигналювання, залежного від рецепторних тирозинових протеїнкіназ, перебудови актинового цитоскелету і адгезії клітин, контролю функцій подоцитів і Т клітин. Оскільки Ruk/CIN85/ SETA містить одно часно SH3 домени і багаті на пролін послідовності на рівні одного поліпептидного ланцюга та С-кінцевий суперспіралізований район, можна припустити, що його біологічна активність регулюється за рахунок внутрішньо- і міжмолекулярних взаємодій. Здатність багатих на пролін мотивів Ruk взаємодіяти з власними SH3 доменами та суперспіралізованої ділянки — опосередковувати олігомеризацію різних ізоформ досліджували за допомогою методу зв'язування in vitro GST-злитих білків. Показано, шр SH3A і, в меншій мірі, SH3B домени Ruk кооперативно взаємодіють із власними багатими на пролін послідовностями, у той час як суперспіралізований район забезпечує олігомеризацію ізоформ. Не виключено при цьому, що SH3C домен чинить конформаційний вплив на суперспіралізований район, обмежуючи, в такий спосіб, ступінь олігомеризації. Нами також встановлено, що здатність екзогенних лігандів взаємодіяти з багатими на пролін мотивами Ruk координовано змінюється протягом TNFa-індукованого апоптозу мієломоноцитарних клітин лінії U937. Ruk/CIN85l SETA is a member of a separate and evolutionary conserved family of adapter I scaffold proteins implicated in apoptic and receptor tyrosine kinases signalling, rearrangement of actin cytoskeleton and cell adhesion, podocyte and T cell functions. Self-regulation through intra- and intercellular interactions can be supposed for RuklCIN85l SETA as this protein contains SH3 domains and proline-rich sequence, localized within one polypeptide chain, as well as C-terminal coiled-coil region. The ability of Ruk proline-rich motifs to interact with its own SH3 domains in an intramolecular fashion and coiled-coil region to mediate oligomerization between different isoforms was assessed in GST pull down experiments. It was shown that both Ruk SH3A and to a less extent SH3B domains can interact with its own proline-rich sequences in a cooperative manner, while coiled-coil region provide for isoforms oligomerization. SH3C domain appear exerts conformational constraints, imposed on coiled-coil region, restricting the level of oligomerization. We also demonstrated that the ability of exogenous ligands to interact with Ruk polyprotine motifs is changing during the course of TNFa-induced apoptosis of human myelomonocytic W37 cells.